Sunset - Kingsbury, Karen (Carol Stream, Ill. : Tyndale House Publishers, 2008)
As John Baxter makes plans to marry Elaine, one of the Baxters enters into the most trying season of all.
Includes discussion questions (p. 313-15).
Keywords: Weddings -- Fiction; Family -- Fiction; Celebrities -- Fiction; Domestic fiction; Christian fiction